Sex-based outcomes on unguided de-escalation from ticagrelor to clopidogrel in stabilized patients with acute myocardial infarction undergoing percutaneous coronary intervention: a post-hoc analysis of the TALOS-AMI - Shin, Eun-Seok; Jun, Eun Jung; Kim, Bitna; Kim, Chan Joon; Park, Mahn-Won; Choo, Eun-Ho; Hwang, Byung-Hee; Lee, Kwan Yong; Oh, Gyu-Chul; Kim, Min Chul; Yim, Hyeon Woo; Ahn, Youngkeun; et al. (Frontiers in Cardiovascular Medicine, 2024)
The TALOS-AMI study highlighted the effectiveness of a de-escalation strategy shifting from ticagrelor to clopidogrel 1 month after percutaneous coronary intervention (PCI), resulting in significant reduction in clinical events, primarily attributed to a substantial decrease in bleeding events. Nevertheless, the impact of this strategy on outcomes based on sex remains unclear.Methods: This was a post hoc analysis of the TALOS-AMI study. At one month after PCI, patients who remained adherent to aspirin and ticagrelor without experiencing major adverse events underwent randomization into either the de-escalation group (clopidogrel plus aspirin) or the active control group (ticagrelor plus aspirin) for an additional 12 months. The primary endpoint encompassed a composite of cardiovascular death, myocardial infarction, stroke, and Bleeding Academic Research Consortium bleeding type 2 or greater at 12 months after randomization.Results: Among the 2,697 patients included in this study, 454 (16.8%) were women. Women, characterized by older age and a higher prevalence of hypertension, diabetes, impaired renal function, and non-ST-segment myocardial infarction, exhibited a lower primary endpoint at 12 months compared to men (adjusted hazard ratio [HR], 0.60; 95% confidence interval [CI], 0.37-0.95; P = 0.03). The de-escalation group versus the active control group demonstrated a reduced risk of the primary endpoint in both women (adjusted HR, 0.38; 95% CI, 0.15-0.95; P = 0.039) and men (adjusted HR, 0.56; 95% CI, 0.40-0.79; P = 0.001) (interaction P = 0.46).In stabilized patients post-PCI with drug-eluting stents for acute myocardial infarction, the primary endpoint was lower among women compared to men. In this cohort, the benefits of an unguided de-escalation strategy from ticagrelor to clopidogrel were comparable in women and men.